Comunidade Ucraniana de Alto Paraíso: permanências e mudanças no processo de reprodução social - Iurckevicz, Claudio (2018)
The presente dissertation approach the process os constitution and development of Ukrainian Community of Alto Paraíso inserted in the contexto of ocupation Paraná’s territory. Following the politicy of the Brazilian government of busy and do to procuce the families were attracted to the new geographic space, the southwest of Paraná, with the possibilite de new Earth at in the more quantity. Migrants of the differents regions of Paraná and Santa Catarina and facing the great difficulties these families formed an one Community with foundation of the Family farming. With the support of the priest of Ordem de São Basílio Magno together with the sister of the congregation Sant’Ana”s established in the own Community they built a story and a structure to experience your Faith and train your children with na academic education and religious and keep your identity as ethnic group. The central purpse of work is notice the changes that occurred over time and the existing stays the forme be and doing of the families that currently live in the community. The reconstitution of the history of the community and the lifting of the actual reality with the interviews carried out with the pioneers, the families and the religious leadership allowed a very broad vision of the community and its transformations that occurred over the years. The changes could be perceived in the way of producing with the changes in the form and the cultures adopted as main and in the way of being, with the preservation of some customs and traditions and with the modification of others, some being even left aside. It was possible to verify the importance of religiosity as an element of union and resistance of families and language as an element of identification of the community as Ukrainian. It should be noted that the community continues its history seeking to remain as an ethnic group, preserving cultural and religious elements and adapting to the new challenges that arise with the new times.